Effects of Operation Conditions on Performance of a Gas Turbine Power Plant - M. M., Rahman; Thamir K., Ibrahim (2010)

(untitled)
This paper presents the effect of operation conditions (compression ratio, turbine inlet temperature, air to fuel ratio and efficiency of compressor and turbine) on the performance of gas turbine power plant. The computational model was developed utilizing the MATLAB codes. Turbine work found to be decreases as ambient temperature increases as well as the thermal efficiency decreases. It can be seen that the thermal efficiency increases linearly with increases of compression ratio while decreases of ambient temperature. The specific fuel consumption increases with increases of ambient temperature and lower turbine inlet temperature. The effect of variation of SFC is more significance at higher ambient temperature than lower temperature. It is observed that the thermal efficiency linearly increases at lower compressor ratio as well as higher turbine inlet temperature until certain value of compression ratio. The variation of thermal efficiency is more significance at higher compression ratio and lower turbine inlet temperature. Even though at lower turbine inlet temperature is decrement the thermal efficiency dramatically and the SFC decreases linearly with increases of compression ratio and turbine inlet temperature at lower range until certain value then increases dramatically for lower turbine inlet temperature.